Invigorasi Benih Terhadap Viabilitas dan Vigor Benih Kacang Tanah (Arachys Hypogaea) - Patriyawaty, Nia Romania; Pratiwi, Herdina (Proceedings Series on Physical & Formal Sciences, 2022)
Seed treatment or so called as seed invigoration is one of effort to increase seed germination (viability) and avoid the attack of disease. This study aimed to examine the effect of peanut seeds tretament using water and Ca(OH)2 solution on growth, viability, and vigor of peanut seeds, which were arranged in a Randomized Block Design consisting of five levels and three replications, namely, P0 (control), P1 (immersion in water temperature of 20-25oC), P2 (immersion with water temperature of 50oC), P3 (immersion with water temperature of 20-25oC + Ca(OH)2), and P4 (soaking with water 50oC + Ca(OH)2). The results showed that the seed soaking treatment significantly affected plant height, root length, germination and vigor index of peanut seeds. Soaking the seeds in water at a temperature of 20-25oC (P1) can give the highest of plant height, percentage of germination and vigor index of 84% and 75% higher, respectively, than without seed soaking treatment. However, the treatment of seed soaking by adding a solution of Ca(OH)2 was able to produce the highest primary root length.